A stereospecifically 18O-labelled deoxydinucleoside phosphate block for incorporation into an oligonucleotide. - Potter, B V (1983)
Fully protected diastereoisomers of deoxyguanylyl (3' leads to 5') deoxyadenosine stereospecifically labelled on phosphorus with oxygen-18 have been synthesized by oxidation of phosphite triester intermediates in the presence of 18O-labelled water. The diastereoisomers have been chromatographically separated and their absolute configuration at phosphorus determined. (Rp)-[18O]deoxyguanylyl (3' leads to 5')deoxyadenosine has been prepared by complete deprotection of the parent diastereoisomer of the Sp configuration. Methylation of the former compound permits assignment of the absolute configurations of the methyl esters of N1-methyldeoxyguanylyl (3' leads to 5') N1-methyldeoxyadenosine.